Influence of Competence and Customer Service Motivation on the Performance of the Bank Syariah Mandiri Remittance Business Unit - Widhi Wicaksono (Universitas Negeri Makassar, 2019)
Customer service plays an important role as the frontline in achieving the remittance business unit target. Bank Syariah Mandiri must be able to guarantee that customer service has adequate competence and high motivation in serving customers. This study aims to analyze the effect of competence and motivation of customer service on the performance of the remittance business unit. The object of research is 124 customer service in the region II Bank Syariah Mandiri. The method used in this study is Ordinary Least Square (OLS) on the SPSS 21 program. The results of this study indicate that the variable of competence and customer service motivation has a positive and significant impact on the performance of the remittance business unit.